Between dark black and light brown. Discourses and ethnic identities among afrodescendant boys and girls in school context in Bogotá - Soler, Sandra (Colombian Applied Linguistics Journal, 2012)
There is a felt need to understand the way ethnic identities are constructed by Afrodescendant boys and girls aged 6-12 in school contexts in Bogotá as there is little research in such specific context and topic in Colombia. This research report proposes a discourse analysis and social psychology approach to tackle such problem. Thus this paper seeks to identify the discursive mechanisms that allow us to know how identity processes emerge from the acceptance or denial of ethnicity; mechanisms that may lead or have an effect on discursive adaptation, resistance or negotiation. Findings suggest that children begin early their ethnic self-identification from the color of the skin, whereby they differentiate a wide color range, tending towards whitening. Children have different degrees of ethnic appraisal that go from pride to rejection. In inter-ethnic relations, they tend to deny or minimize the conflict, and there is a tendency to avoid speaking about it. Children identify the cause of the problem as a quantitative issue, as they are minority in Bogotá. In inter-ethnic dynamics, some children accept the stereotypes assigned to them, others reject them, and others scoff at them.